PSYCHOLOGICAL ASPECTS OF SEXUAL DYSFUNCTIONS - Silveira Meireles, Gabriela (2019)
A sexual health is becoming increasingly important when we think of the longevity of these affective relationships, making part of two global individuals and in their sense of being-living. However, as sexual dysfunctions it was feito muito present both in homens quanto em mulheres. The objective of this article is to disclose Clinical Sexology in its historical aspect to contextualize sexual dysfunctions in order to establish the main male and female dysfunctions and to understand the psychological aspects that produce sexual dysfunctions. The theoretical reference given includes mainly scientific productions two fields of education and education, with a focus on psychological research. The main authors used in this research: Abdo (2004, 2006); Abdo and Fleury (2006); Alves (2013); Béjin (1987); Cavalcanti, Serrano and Lopes (2005); Carvalheira and Allen-Gomes (2002); Figueiró (1998); Fonseca, Soares and Vaz (2001); Foucault (2006); Giami (2019); Hall and Instituto Pedagógico de Minas Gerais (2019); Irvine (2005); Lata et al. (2008); Nobre (2005, 2010); WHO (1993); Russo et al. (2009, 2011); Russo (2012); Weeks (2002). The results obtained with this survey about the subject allowed us to conclude that there are many different psychological influences in the production and / or maintenance of sexual dysfunctions, so that at the same time the psychologist will be able to face these patients. It is concluded, assim, that a psychotherapy focused on sexology and a fundamental resource for the  promotion of two individuals.